2019
DOI: 10.1021/acs.jpca.8b10819
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Turing Patterns in the CDIMA Reaction by Ultraviolet and Visible Light

Abstract: We have carried out the first systematic study of the effects of ultraviolet light, both alone and in combination with visible white light, on Turing patterns in the chlorine dioxide–iodine–malonic acid (CDIMA) reaction. The ultraviolet light used has a sharp peak at 368 nm and can perturb the system selectively. It primarily decomposes chlorine dioxide in a zeroth-order reaction, and when it is used to illuminate Turing patterns, shrunken spots are formed with an imperfect hexagonal arrangement. The ultraviol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Many recent studies of chemical Turing patterns use the CDIMA reaction in a CFUR, where the patterns form in a quasi-two-dimensional gel with one-sided feeding [14,41,45,46]. A schematic for the experimental setup is shown in [14].…”
Section: The Chlorine Dioxide-iodine-malonic Acid Reactionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many recent studies of chemical Turing patterns use the CDIMA reaction in a CFUR, where the patterns form in a quasi-two-dimensional gel with one-sided feeding [14,41,45,46]. A schematic for the experimental setup is shown in [14].…”
Section: The Chlorine Dioxide-iodine-malonic Acid Reactionmentioning
confidence: 99%
“…In general, the wavelength of Turing patterns generated by the CDIMA reaction varies inversely with the chlorine dioxide concentration [45,51] and is typically on the order of several hundred micrometres. Gaskins et al [41] showed that other chemical species added to the system can strongly influence the pattern wavelength.…”
Section: The Chlorine Dioxide-iodine-malonic Acid Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 In addition, light as an external control parameter is particularly appealing in the study of nonlinear chemical reactions due to the easy tunability of intensity and spectral composition. [9][10][11] Many chemical oscillators are known to be sensitive to light irradiation, showing photoinduction and photoinhibition behavior in homogeneous and inhomogeneous systems. In the Ru(bpy) 3 2+ -catalyzed Belousov-Zhabotinsky (BZ) oscillator, the oscillatory frequency was inuenced by the illumination intensity, 12 while the rotating spiral waves transform to a labyrinthine standing-wave pattern by periodic light-perturbation.…”
Section: Introductionmentioning
confidence: 99%
“…13 By virtue of the process, photophobic and phototropic movements of a self-oscillating gel hosting the photosensitive BZ reaction were designed to approach its favorable environments spontaneously. 14,15 In another case, the photosensitive dissociation of molecular iodine was utilized in the chlorine dioxideiodine-malonic acid (CDIMA) reaction, Briggs-Rauscher reaction, and Bray-Liebhafsky reaction, leading to the cessation or promotion of oscillations, [16][17][18] and pattern structures modulation 11,19,20 under the forcing of light illumination.…”
Section: Introductionmentioning
confidence: 99%